Ganoderma applanatum polysaccharides and ethanol extracts promote the recovery of colitis through intestinal barrier protection and gut microbiota modulations. Issue 2 (22nd December 2021) - Li, Miaoyu; Yu, Leilei; Zhai, Qixiao; Liu, Bingshu; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Tian, Fengwei
Abstract : Inflammatory bowel disease is associated with intestinal homeostasis dysregulation and gut microbiota dysbiosis. Abstract : Inflammatory bowel disease is associated with intestinal homeostasis dysregulation and gut microbiota dysbiosis. This study aimed to investigate the protective effect of Ganoderma applanatum extracts ( G. applanatum polysaccharides (GAP) and 75% ethanol extracts (GAE)) on colon inflammation and elucidate the therapeutic mechanism. GAP and GAE showed considerable protective effects against dextran sodium sulfate (DSS)-induced colitis, as demonstrated by reduced mortality, body weight, disease activity index score, colon length, and histological score. Through GAP and GAE administration, the destroyed intestinal barrier recovered to normal, as did intestinal inflammation. We also confirmed that GAP administration promoted the recovery of colitis in a gut microbiota-dependent manner. The similarity between GAP and GAE administration was that they both altered the disordered gut microbiota damaged by DSS, exhibiting reduced abundance of Escherichia _ Shigella, Enterococcus, and Staphylococcus, but the modulation of the gut microbiota was distinct between GAP and GAE.